UJI EFEKTIVITAS SARI BUAH KURMA (PHOENIX DACTYLIFERA) TERHADAP JUMLAH TROMBOSIT MENCIT JANTAN (MUS MUSCULUS L) YANG DIBERI KOTRIMOKSAZOL - PUTRI NADIA; YENITA YENITA; CUT MOURISA; ISRA THRISTY (JURNAL ILMIAH KOHESI, 2023)
Date palm suspension (Phoenix dactylifera) is a processed product from date palm, which has various ingredients that are beneficial for health. There was a study about the effectiveness of date palm suspension which aims to determine the effectiveness of date palm suspension to increasing the number of platelets in male mice (Mus musculus L) that given cotrimoxazole. This research use an experimental study with "Post test only control group design" and "Simple randomized sampling". This study used 35 male mice aged 2-3 months, weighing 20-30 grams were divided into 5 groups randomly. Negative control group, positive control group, and treatment group (I, II, III) with dose of 7 mg/kgBW, 14 mg/kgBW, 21 mg/kgBW. Cotrimoxazole was given for 8 days and date palm suspension was given for 2 days, then the platelet count was checked using an Automated Hematology Analyzer. The effectiveness of date palm suspension to increasing the platelet count of each test group was analyzed with One Way ANOVA statistical test. The results of statistical tests showed that date palm suspension with dose of 7 mg/kgBW, 14 mg/kgBW, 21 mg/kgBW could increase the platelet count of male mice that given cotrimoxazole, resulting in p<0.05 in all groups. Date palm juice (Pheonix dactylifera) is effective in increasing platelet levels, especially at a dose of 21 mg/kgBW. Keywords: Cotrimoxazole, Date palm suspension (Phoenix dactylifera), Platelets.